Targeting endothelial ERG to mitigate vascular regression in retinopathies - Eric Ma; Christopher M. Schafer; Jun Xie; Yelyzaveta Rudenko; John T. H. Knapp; Anna M. Randi; Graeme M. Birdsey; Courtney T. Griffin (Proceedings of the National Academy of Sciences, 2025)
Retinopathy of prematurity (ROP) and diabetic retinopathy (DR) are ocular disorders in which an initial loss of retinal capillaries leads to damaging tissue ischemia followed by a compensatory neovascularization response that generates pathological capillaries in the eye. Using a mouse model of ROP and samples from DR patients, we found that the highly homologous and homeostatic erythroblast transformation-specific (ETS) family transcription factors ETS-related gene (ERG) and Friend leukemia integration 1 (FLI1) are downregulated in endothelial cells (ECs) of retinal capillaries prior to their regression in early stages of these diseases. We developed a mouse model of inducible EC-specific overexpression of Erg and found it mitigates capillary regression, retinal neuron death, neovascularization, and visual defects in the ROP model. Erg overexpression also reduces capillary regression in early stages of a murine DR model. We next found that simultaneous deletion of endothelial Erg and Fli1 is sufficient to promote regression of the pathological retinal capillaries that arise in late stages of the ROP model. Altogether, our data demonstrate that deletion of homeostatic endothelial ETS factors promotes capillary regression, while maintenance of even one of these factors prevents regression. These findings offer insights into approaches for preventing and treating retinopathies at different stages of these diseases.